The Impact of Polycystic Ovary Syndrome on the Sporting Performance of Female Players - Ahmad, Bilal; Zahra, Syeda Maryam (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2020)
Polycystic Ovary Syndrome (PCOS) is perhaps the most widely recognized endocrine issues in females of reproductive age, influencing up to 20% of individuals of this populace. Many recent studies indicate that testosterone, which can increase muscle mass and strength, stimulates erythropoiesis, promotes competitive behavior, and enhances sporting performance of female athletes. Methods: The comparative study was designed and conducted in which a sample of female athletes (n=40) who had been diagnosed with PCOS by a qualified gynecologist based on clinical features and lab tests. At the same time, a healthy group of female athletes (n=40) was selected from participants of the same population and having regular menses and showing no clinical features of PCOS. The main objectives of the study included: 1) to compare both the groups of female athletes on clinical features of PCOS, and 2) to compare both the groups on self-perceived sports performance. Data was collected from The University of Central Punjab, The University of Lahore, and The University of Lahore College for Women. Data collection was done using two different instruments involving “Polycystic Ovary Syndrome Questionnaire (PCOSQ)” and “Athlete’s Subjective Performance Scale (ASPS)”. Data analyses involved descriptive analysis followed by “Independent Sample t test’ to compare the physical and psychological impact of PCOS and ANOVA was applied to analyze the impact of PCOS on sports performance. Results: There were significant differences between female athletes with PCOS and those with Non-PCOS on physical and psychological conditions. Weight issues t (78) =15.104, (p= .000), Body Hair t (78) =25.108, (p= .000), Menstrual Problems t (78) =20.976, (p= .000), Helplessness t (78) =17.775, (p= .000), and Low mood t (78) =8.449, (p= .000). Significance value (p = .000), which is below 0.05 and, therefore, there is a statistically significant difference in the mean sporting performance. Conclusion: Based on the results, it can be concluded that female athletes with PCOS were more concerned about their physical and psychological conditions. Moreover, their sporting performance was statistically significantly higher than Non-PCOS athletes, which is attributed to higher energy level caused by PCOS itself. Future research must focus on measuring energy level of female athletes with PCOS and Non-PCOS.